1995
DOI: 10.1099/00207713-45-2-400
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Characterization and Emended Description of Methanolobus vulcani

Abstract: Methanolobus vulcani PL-12/MT (T = type strain) grew on methylamines and methanol but not on dimethyl sulfide, formate, acetate, or H,-CO,. The cells grew rapidly at mesophilic temperatures, at neutral pH values (pH 6 to 7.5), and in medium supplemented with 0.1 to 1.2 M NaCl and 13 mM M$+. The cells grew in mineral medium containing biotin and a catabolic substrate, but growth was stimulated by yeast extract and peptones. M. vulcani was physiologically similar to Methanolobus tindarius and had a similar 16s r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Phylogenetically, A8p was most closely related to Methanobacterium formicicum (97.2 YO similarity). However, this evolutionary distance is sufficiently large that the two strains most probably belong in separate species (7,12,19,41). The phenotypic characteristics of A8p confirmed that the isolate belongs to the genus Methanobacterium and that it can be distinguished from phylogenetically related taxa as shown in Table 2.…”
Section: Discussionmentioning
confidence: 63%
“…Phylogenetically, A8p was most closely related to Methanobacterium formicicum (97.2 YO similarity). However, this evolutionary distance is sufficiently large that the two strains most probably belong in separate species (7,12,19,41). The phenotypic characteristics of A8p confirmed that the isolate belongs to the genus Methanobacterium and that it can be distinguished from phylogenetically related taxa as shown in Table 2.…”
Section: Discussionmentioning
confidence: 63%
“…M. barkeri is a metabolically versatile methanogen and can grow on hydrogen, methylated compounds, methanol, or acetate (70,71), while M. vulcani uses only methanol as a growth substrate (72). However, in the presence of elemental sulfur, as detected at the biofilm-metal interface in the corroding piping section, these methanogens, as well as Methanobacterium species, can switch their metabolism to dissimilatory elemental sulfur reduction and produce high concentrations of hydrogen sulfide (73), potentially contributing to CMIC in this way (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Sequences of OTU 11 could be classified to the genus Methanolobus and were closely related to Methanolobus vulcani (98%), which is halotolerant and uses methyl-group containing substrates for growth (Kadam and Boone 1995). Sequences of OTU 12 were assigned to the genus Methanoculleus with a high similarity to Methanoculleus marisnigri (97%) (Romesser et al 1979) and Methanoculleus palmolei (98%) (Zellner et al 1998 rDNA of Methanobacterium curvum (96%, OTU 13) (Sun et al 2001), a hydrogenotrophic methanogen.…”
Section: Analyses Of Clone Librariesmentioning
confidence: 99%